Utility of 24-hour pharyngeal pH monitoring and clinical feature in laryngopharyngeal reflux disease. (4th March 2019) - Wang, Gang; Qu, Changmin; Wang, Lei; Liu, Hongdan; Han, Haolun; Xu, Bingxin; Zhou, Ying; Li, Baowei; Zhang, Yiyan; Sun, Zhezhe; Gong, Jing; Li, Lianyong; et al.
Abstract: Background: pH monitoring can reflect the changes in H + in the airway. Objectives: To explore the utility of pharyngeal pH monitoring in the diagnosis of laryngopharyngeal reflux disease (LPRD). Material and methods: Clinical data from 956 suspected LPRD patients from February 2016 to March 2018 were analyzed retrospectively. Results: One hundred forty-one patients had positive Ryan score. The positive rates of reflux symptom index (RSI), reflux finding score (RFS), RSI and RFS and RSI or RFS were 14.7%, 32.5%, 21.9%, 7.8% and 46.5%, respectively. The RFS in the positive Ryan score group was higher than that in the negative Ryan score group [(6 ± 3.5) vs. (4.8 ± 2.9)], while the RSI was not significantly different from that in the negative Ryan score group [(10.9 ± 8) vs. (11.3 ± 7.1)]. Regarding Ryan score as the gold standard in the diagnosis of LPRD, the sensitivity, specificity, positive and negative predictive value of identifying LPRD by RSI/RFS were 15.9%, 86.3%, 50.4% and 54%, respectively. Conclusions: Ryan score, RSI and RFS have poor correlation in detecting LPRD. Some patients may be missed with the Ryan score as a diagnostic criterion. Significance: Pharyngeal pH monitoring is useful and more appropriate index is expected.